A fjord with a land-terminating glacier: Meltwater, bio-optics, particulate matter, nutrients, phytoplankton species, and primary production in west Greenland - Lars Chresten Lund-Hansen; Ingela Dahllöf; Morten Holtegaard Nielsen (Zenodo, 2023)
The paper describes the bio-optical conditions, particulate matter, nutrients and primary production in a west Greenland fjord with a land-terminating glacier